Virtual Reality Applications in Remote Physical Therapy and Rehabilitation: A Digital Health Revolution - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The landscape of physical therapy and rehabilitation is undergoing a profound transformation, driven by the convergence of digital health technologies and ar...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Telemedicine